The Effect Of Audio-Visual-Based Education About Spinal Anesthesia On The Level Of Anxiety Of Pre-Operative Patients At Kardinah Tegal Hospital - Ihyaul Arofah; Amin Susanto; Atun Raudotul Ma’rifah (International Journal of Health Engineering and Technology, 2026)
Preoperative anxiety is a condition that can potentially endanger patients and is often caused by a lack of information regarding anesthesia procedures. The advancement of technology enables the delivery of health education through audiovisual media that combines moving images and sound. At RSUD Kardinah Tegal, preoperative education is still delivered through anesthesia information forms and has not yet utilized video-based media. This study aims to analyze the effect of audiovisual-based education about spinal anesthesia on the level of preoperative patient anxiety at RSUD Kardinah Tegal. This study employed a quantitative method with a quasi-experimental design using a pretest-posttest with control group approach. The sample consisted of 76 respondents divided into intervention and control groups, each consisting of 38 respondents, selected using a non-probability purposive sampling technique. The anxiety level was measured using the APAIS scale. Data analysis was conducted using the Wilcoxon test and Mann–Whitney U test. The results showed that before the intervention, most respondents in the intervention group experienced severe anxiety (78.9%), while in the control group it was 92.1%. After the audiovisual education was provided, anxiety levels in the intervention group decreased to mild anxiety (76.3%), whereas the control group mostly remained at moderate anxiety (55.3%). There was a significant difference in anxiety levels between the two groups (p-value = 0.001 < 0.05).In conclusion, audiovisual-based education is effective in reducing preoperative anxiety levels in patients undergoing spinal anesthesia at RSUD Kardinah Tegal.